Power that Builds Others and Power that Breaks: Effects of Power and Humility on Altruism and Incivility in Female Employees. Issue 1 (2nd January 2018) - Yoon, David J.; Farmer, Steven M.
ABSTRACT: Building on the approach/inhibition theory of power and the situated focus theory of power, we examine the roles of positional and personal power on altruism and incivility in workplace dyads. Results from a field study in daycare centers showed that legitimate power (a dimension of positional power) was positively associated with incivility. In contrast, personal power—referent power and expert power—was positively associated altruism and was negatively associated with incivility. Referent power was a stronger predictor of both altruism and incivility for individuals with low humility than those with high humility. Coercive power was a stronger predictor of incivility for individuals with high humility than those with low humility.